Cognitive behaviour therapy (CBT) for children with reading difficulties : A case study - Julia Ai Cheng, Lee; Ting, Chuong Hock (2023)
Background: Children with reading difficulties are at risk for vicious cycles of struggles, failure, demoralization, lack of interest in school, emotional difficulties such as anxiety and frustration, behavioural problems, and psychosocial maladjustments. The cycles of academic struggles lead to further academic failure, psychosocial, and behavioural problems. These risk factors are developmentally cumulative across grades starting early in preschool and primary school. Interventionists such as educational therapists of children with specific learning disabilities are faced with challenges in providing holistic solutions that focus on both the academic and cognitive-behavioural needs of children. Cognitive behaviour therapy is an under-explored approach when conducting educational therapy for children with SLD.